FIGURATIVE LANGUAGE OF METAPHORS IN THE HOLY QURAN - Mutammam Mutammam; Aisyah Zubaidah (Jurnal Alsinatuna, 2016)
As a system of communication, language has literal and figurative meanings. In the case of literal language, words are used to express meaning as defined, while in the case of figurative language, words are used to provide room for interpretation. A profound contemplation done by some linguists shows that Holy Qur’an uses two kinds of meanings, they are haqiqi (literal language) and majazi (figurative languages). In this case, metaphors or figurative language is used as a persuasive device to strengthen Muslims’ faith in God and convince disbelievers to believe in God.